Formation of Murāqabah Character through Reflection on Smartphone Use in Islamic Religious Education Learning - Badrus Shalih; Nuril Anwar; Al-Qanit Qurba (Khalaqa: Journal of Education and Learning, 2026)
The presence of smartphones in Islamic Religious Education classrooms has created a moral and pedagogical paradox. Smartphones support access to Qur'anic texts, digital learning materials, and assignment platforms; at the same time, notifications, entertainment applications, and copy-paste habits may weaken attention, honesty, and self-control. This article examines the formation of murāqabah character through reflective smartphone use in Islamic Religious Education. Using a descriptive qualitative case-study design, the study draws on classroom observation, semi-structured interviews with an Islamic Religious Education teacher, Grade VI students at Madrasah Ibtidaiyah Miftahul Ulum Desa Panyiuran, Kabupaten Banjar, South Kalimantan, and a homeroom teacher, as well as students' reflective notes. The findings show that smartphone reflection helps students move from externally controlled obedience to inner awareness. Murāqabah becomes more concrete when students connect the idea that Allah watches human actions with everyday digital practices, such as opening unrelated applications, checking notifications, copying answers from the internet, and sharing religious content without verification. The study contributes theoretically by proposing murāqabah digital as a form of spiritual self-regulation in technology-mediated learning. Contextually, it offers a practical model for Islamic Religious Education teachers to cultivate digital adab without relying only on prohibition or surveillance.